Physiological effects of feeding whiteleg shrimp (Penaeus vannamei) with the fresh macroalgae Chaetomorpha clavata - Borges, Emanuelle Pereira [UNESP]; Machado, Levi Pompermayer [UNESP]; Louzã, Ana Carolina [UNESP]; Ramaglia, Andressa Cristina [UNESP]; Santos, Michelle Roberta [UNESP]; Augusto, Alessandra [UNESP] (Elsevier, 2024)
In shrimp farming, the use of commercial feed can generate high nutrient loads in water bodies, and often constitute the most substantial component of production costs. Alternatives that seek to reduce the use of commercial feed can therefore both mitigate environmental impacts and reduce operational expenses. One possible strategy is incorporation of algae that crustaceans can consume with minimal biological effect into integrated multi-trophic aquaculture (IMTA) systems. Our objective was to determine whether the marine shrimp Penaeus vannamei feeds on the fresh macroalga Chaetomorpha clavata and whether the partial substitution (50 %) of this alga in its diet influences its physiology. Survival, growth, and a range of physiological processes including ingestion, defecation, metabolism, nitrogen excretion, oxidized energy substrate, hepatosomatic index, and energy budget were assessed in P. vannamei shrimp fed commercial feed (100 %, control) versus shrimp fed a combination of commercial feed and algae (50 % each). Our results showed that P. vannamei fed on C. clavata, and that there were no significant differences in mortality and growth rates (∼11 %) between shrimp fed with the two diets. The ingestion rate was higher in the group fed with macroalgae, however the defecation rate and digestibility were not affected. In both groups, no differences were detected in metabolic rates, growth, nitrogenous excretion, and egestion between shrimp fed the different diets, nor in oxidized energy substrates and the hepatosomatic index. Our results show that substituting 50 % of the feed with C. clavata represents a viable alternative to full commercial feed since it had minimal impact on the physiological functions of P. vannamei. In addition to the economic benefit of reducing the amount of feed used during culture, the use of algae also reduces contamination of effluent water, thereby improving environmental sustainability and water quality.
Keywords: Aquaculture; Crustacean; Physiology; Seaweed